The cholinergic selectivity of FDA-approved and metabolite compounds examined with molecular-docking-based virtual screening - Gambardella, M.D.; Wang, Y.; Pang, J. (Molecules, 2024)
The search for selective anticholinergic agents stems from varying cholinesterase levels as Alzheimer’s Disease progresses from the mid to late stage. In this computational study, we probed the selectivity of FDA-approved and metabolite compounds against acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) with molecular-docking-based virtual screening. The results were evaluated using locally developed codes for the statistical methods. The docking-predicted selectivity for AChE and BChE was predominantly the consequence of differences in the volume of the active site and the narrower entrance to the bottom of the active site gorge of AChE. © 2024 by the authors.
Keywords: FDA; acetylcholinesterase; butyrylcholinesterase; cholinesterase; dept.che; metabolites; molecular docking; molecular dynamics; peer-reviewed; statistical analyses; virtual screening; visualization